2007
DOI: 10.4070/kcj.2007.37.12.630
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical and Angiographic Outcomes of Compromised Side Branches (Stent Jail) after Percutaneous Coronary Intervention between Sirolimus-Eluting Stents and Paclitaxel-Eluting Stents

Abstract: Background and Objectives: Drug-eluting stents (DES) have been used worldwide for conducting safe and effective percutaneous coronary intervention (PCI) for treating coronary artery disease. However, the DES might cause a higher frequency of an acute side branch occlusion or stent jails near the target lesion after PCI than that with using bare metal stents (BMS). This may be due to the eluted drug or the thick stent struts. We evaluated the clinical and angiographic outcomes of compromised side branches (sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
(14 reference statements)
3
0
0
Order By: Relevance
“…There was no mortality or emergency CABG within 24 hours during the in-hospital period both in group I and group II. These findings were consistent with study done by Dehghani et al, 14 Lee et al, 13 Ghayemain et al, 11 Cho et al 7 and Nozari et al 15 Dehghani et al 14 reported in their study that during hospital stay the incidence of major adverse cardiac events (MACE) comprising death, need for target vessel revascularization, and Q-wave MI was almost similar in the patients with and in those without acute side branch occlusion. Lee et al 13 found that there were no clinical in-hospital events for either group.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…There was no mortality or emergency CABG within 24 hours during the in-hospital period both in group I and group II. These findings were consistent with study done by Dehghani et al, 14 Lee et al, 13 Ghayemain et al, 11 Cho et al 7 and Nozari et al 15 Dehghani et al 14 reported in their study that during hospital stay the incidence of major adverse cardiac events (MACE) comprising death, need for target vessel revascularization, and Q-wave MI was almost similar in the patients with and in those without acute side branch occlusion. Lee et al 13 found that there were no clinical in-hospital events for either group.…”
Section: Discussionsupporting
confidence: 82%
“…These findings were consistent with study done by Dehghani et al, 14 Lee et al, 13 Ghayemain et al, 11 Cho et al 7 and Nozari et al 15 Dehghani et al 14 reported in their study that during hospital stay the incidence of major adverse cardiac events (MACE) comprising death, need for target vessel revascularization, and Q-wave MI was almost similar in the patients with and in those without acute side branch occlusion. Lee et al 13 found that there were no clinical in-hospital events for either group. Ghayemain et al 11 demonstrated that the incidence of complications in patients with compromising side branches smaller than 2 mm is small, compromising side branches larger than 2 mm can be accompanied by clinical outcomes as non Q-wave MI.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation